GEN Y PREFERENCES FOR GREEN HOTELS: A BEHAVIORAL ANALYSIS OF SUSTAINABLE HOSPITALITY - Truong Thi Lan Huong; Phung Ai Vi (HUIT Journal of Science, 2025)
This study investigates the key factors shaping Gen Y customers’ preferences for green hotels in Ho Chi Minh City, highlighting the pivotal role of intention to choose in driving overall satisfaction. Despite the higher costs often associated with eco-friendly accommodations, Gen Y travelers are increasingly adopting environmentally conscious consumption habits. Drawing on the American Customer Satisfaction Index (ACSI) and the Theory of Planned Behavior (TPB), this research develops a conceptual framework to examine how awareness, perceived value, and trust influence Gen Y’s intention to select green hotels and, subsequently, their satisfaction. A quantitative survey of 347 Gen Y visitors to Ho Chi Minh City reveals that awareness, perceived value, and trust significantly shape intention to choose, thereby enhancing satisfaction with green hotels. By identifying the behavioral and psychological drivers of Gen Y’s preferences for sustainable hospitality, this study enriches consumer behavior theory. It also advances the literature on green hotels by demonstrating the need to integrate environmental sustainability with customer experience to boost perceived value. These findings provide strategic insights for green hotel marketing and development, aligning with Gen Y’s sustainability expectations. The study offers managerial recommendations, emphasizing the importance of enhancing perceived value, building trust, and raising awareness to foster intention to choose and improve customer satisfaction.